Curcumin and Mesenchymal Stem Cells Ameliorate Ankle, Testis, and Ovary Deleterious Histological Changes in Arthritic Rats via Suppression of Oxidative Stress and Inflammation - Rania H. Ahmed; Sanaa R. Galaly; Nadia Moustafa; Rasha Rashad Ahmed; Tarek M. Ali; Basem H. Elesawy; Osama M. Ahmed; Manal Abdul-Hamid (Hindawi Limited, 2021)
Rheumatoid arthritis (RA) is a chronic inflammatory condition, an autoimmune disease that affects the joints, and a multifactorial disease that results from interactions between environmental, genetic, and personal and lifestyle factors. This study was designed to assess the effects of curcumin, bone marrow-derived mesenchymal stem cells (BM-MSCs), and their coadministration on complete Freund's adjuvant- (CFA-) induced arthritis in male and female albino rats. Parameters including swelling of the joint, blood indices of pro-/antioxidant status, cytokines and histopathological examination of joints, and testis and ovary were investigated. RA was induced by a single dose of subcutaneous injection of 0.1 mL CFA into a footpad of the right hind leg of rats. Arthritic rats were treated with curcumin (100 mg/kg b.wt./day) by oral gavage for 21 days and/or treated with three weekly intravenous injections of BM-MSCs (1×106 cells/rat/week) in phosphate-buffered saline (PBS). The treatment with curcumin and BM-MSCs singly or together significantly (P<0.05) improved the bioindicators of oxidative stress and nonenzymatic and enzymatic antioxidants in sera of female rats more than in those of males. Curcumin and BM-MSCs significantly (P<0.05) improved the elevated TNF-α level and the lowered IL-10 level in the arthritic rats. Furthermore, joint, testis, and ovary histological changes were remarkably amended as a result of treatment with curcumin and BM-MSCs. Thus, it can be concluded that both curcumin and BM-MSCs could have antiarthritic efficacies as well as protective effects to the testes and ovaries which may be mediated via their anti-inflammatory and immunomodulatory potentials as well as oxidative stress modulatory effects.